Competence-based curriculum in the in-service teacher vocational education: contributions from finnish programs - Vieira, Azenaide Abreu Soares; Chediak, Sheylla (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2018)
This paper aims at presenting the curricular structure of the Finnish Continuing Education Program for Brazilian trainers, named “FiTT - Finnish Training the Trainers” as well as a course created on the same basis, entitled RE-MAES: Network of Trainers of Active Learning Methodologies centered on the 21st Century student. In addition to discussing the programs, the objective is to investigate how RE-MAES course, designed and developed by Brazilian educators and based on the knowledge constructed throughout FiTT course in Finland, approaches or distances from FiTT program to meet local reality. This research may contribute to the creation of the Brazilian "way" to provide teacher continuing education, which is relevant since there is a need to rethink and reconstruct teacher development courses in Brazil in order to align them with the emerging paradigm of active learning. This research is characterized as qualitative, descriptive and explanatory. Data have emerged from the pedagogical projects of the programs, materials built by the trainers and the researchers’ observations, who have been performing as active participants, certified by the FiTT program and accredited as RE-MAES trainers. The study theoretical framework considers some Finnish education cornerstones, which advocate the alignment of teaching and assessment methods with learning objectives, based on competence-based education concepts, as well as student-centered and active learning paradigms. The study shows that in the dynamics of thinking about the experience and knowledge distribution strategies, the context reality is decisive in the course design, constituting a resignified model of teacher education that responds to the participants’ peculiarity.